CLINICOPATHOLOGICAL FEATURES OF LIVER TUMOURS: A TEN-YEAR STUDY - Taghipour Zahir, Shokouh; Aalipour, Ezatollah; Vakili, Mahmoud; Gane, Mohammad Davoud (Journal of Ayub Medical College Abbottabad, 2015)
Background: Various diseases affect the liver, among them, malignant and benign tumours with hepatic nodules are the most important. We aimed to evaluate the clinicopathological findings related to hepatic tumours and nodules. Methods: This retrospective study was carried out during November 2014 to August 2015 by reviewing the hospital medical records of 164 registered patients with liver biopsies referred to Shahid Sadoughi educational General Hospital, Yazd, Iran, between 2004 and 2014. The samples were selected through the census method. Age, gender, clinical symptoms, initial clinical diagnosis, pathology reports and ultrasound results were considered as variables. Data were analysed by using SPSS-17. Results: There were 87 (53%) men and 77 (47%) women. The mean ages of presentation for malignant and benign tumours were 57.9±17.2 and 44.9±19.4 years, respectively. Seventy benign tumours and 147 malignant tumours were recorded. The most frequent chief complaint was abdominal pain (54.9%) in both malignant (56.50%) and benign tumours (41.20%). Hepatocellular carcinoma (HCC) and hemangioma were the most prevalent malignant and benign hepatic tumours, respectively. In our study, correlation between pathology reports and primary diagnoses was 40.9%, and a significant relationship was found between sonography and pathological findings (p=0.038). Conclusions: We found that only when primary clinical diagnosis and sonography were in favour of malignancy, they were correlated with pathology results. Clinicopathological assessments can help physicians in their diagnosis in order to facilitate the management of hepatic tumours.